Allograft hemorrhage as a manifestation of carbapenem-resistant Klebsiella pneumonia infection in kidney transplant recipients: Case series. Issue 13 (March 2020) - Wang, Zhen; Qian, Yeyong; Bai, Hongwei; Yang, Jintao; Li, Xiang
Abstract: Rationale: Carbapenem-resistant Klebsiella pneumonia (CRKP) infections have been a concerning threat, especially in organ transplant patients with very high mortality. Allograft hemorrhage associated with CRKP infection has never been described. Patient concerns: A total of 6 recipients tested positive for CRKP were identified in 297 adult kidney transplant recipients who received kidney from donors according to Chinese type donation after cardiac death (DCD) at our center between January 2006 and December 2017. Diagnoses: CRKP identification was performed via Vitek 2 system, and the susceptibility was tested by broth microdilution and disk diffusion. Based on the signs of infection and the positive culture, the diagnosis of CRKP infection was established. Interventions: Therapy with antibiotic such as including ceftazidime-avibactam or tigecycline and surgical control of primary infection source including allograft nephrectomy and/or thorough debridement was administrated. Outcomes: The most striking aspect was that spontaneous recurrent hemorrhage occurred in all the 6 patients. The mortality of CRKP infection in our study was 50%. Lessons: CRKP infection possibly due to donor-to-recipient transmission in DCD kidney transplants was essentially a necrotic hemorrhagic inflammation and characterized by recurrent hemorrhage and high mortality. The pre-donation screening for CRKP colonization should be mandatory and, if positive, donation should be contraindicated. And, the effective infection source control such as allograft nephrectomy and/or thorough debridement was important to improve outcomes. Further investigation will be required to further characterize the clinical efficacy of new pharmacotherapeutic schemes including ceftazidime-avibactam.